Peningkatan Kompetensi Lulusan dalam Bentuk Praktik Kerja Lapangan Integratif di Dunia Usaha dan Dunia Industri (DUDI) pada Pegadaian Syariah Kota Pontianak - Azimi, Aulia; Ramanda Saputra; Fina Wahyu Widiastuti; Ratna Ratna; M. Khamim Jazuli; M. Naufal Fahri; Nadia Ulfah (Universitas Kristen Indonesia Toraja, 2025)
In the midst of the rapid development of science and technology, graduates are required to be prepared to face the business world of the industrial world. To face this phenomenon, it is necessary to strengthen graduate competencies in the form of PKL. This form of graduate competency aims to enable graduates to compete and have an overview of the business world of the industrial world. The method in this study is a case study and field with a qualitative approach. The results of community service at the Pontianak City Sharia Pawn Office are that graduates have knowledge of sharia pawn products, assist in the flow of the sharia pawn process, observe the appraisal of pawn goods, assist in transaction administration, study and explain products, assist in the financing disbursement process, observe the auction process, risk management, and carry out marketing activities. The findings are: The Sharia Pawn Office should further increase the socialization of sharia products to the public to expand the market, optimize the use of IT in customer service to increase efficiency and conduct periodic training for employees related to the development of sharia products and services.